Variables associated with the attainment of the highest administrative position in academic libraries in Metro Manila - Dharmawardhana, Nadheera (1991)
This study aims to identify the personal and professional characteristics of academic library administrators in Metro Manila and to correlate the relationship of these characteristics to their attainment of the highest administrative position.